Does Uncovered Interest Rate Parity Hold in Turkey? - Karahan, Ozcan; Çolak, Olcay (International Journal of Economics and Financial Issues, 2012)
Most of the earlier empirical studies focusing on developed countries failed to give evidence in favor of the Uncovered Interest Rate Parity (UIP). After intensive financial liberalization processes and mostly preferred free exchange rate regimes, a new area of research starts to involve the investigation whether UIP holds for developing economies differently. Accordingly, we tested the UIP for Turkey’s monthly interest rate and exchange rate data between 2002 and 2011. We run conventional regressions in the form of Ordinary Least Squares (OLS) and used a simple Generalized Autoregressive Conditional Heteroskedasticity (GARCH) analysis. The empirical results of both methods do not support the validity of UIP for Turkey. Thus, together with most of the earlier empirical studies focusing on developed countries and detecting the invalidity of UIP, we can argue that the experience of Turkey and developed economies are not different. Keywords: Uncovered Interest Rate Parity; OLS; GARCH JEL Classifications: C12; C22; E43